2010
DOI: 10.2968/066003007
|View full text |Cite
|
Sign up to set email alerts
|

It’s Time to Give Up on Breeder Reactors

Abstract: reactor that could produce more plutonium than it consumed (dubbed a "breeder reactor") was first raised during World War II by scientists in the U.S. atomic bomb program. They were concerned that uranium 235, the rare chainreacting isotope that fuels today's nuclear reactors, was insufficiently abundant on Earth to support a large-scale deployment of nuclear power. Over the next 20 years, Britain, France, Germany, India, Japan, and the Soviet Union followed the United States in establishing national plutonium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 3 publications
0
13
0
Order By: Relevance
“…The neutrons propagating the chain reaction remain energetic, or fast. Fast reactors are more flexible in the type of fuel they can consume and can, for example, use uranium-238 as fuel, which is 140 times more abundant than uranium-235 (Cochran et al 2010). 4.…”
Section: Notesmentioning
confidence: 99%
See 2 more Smart Citations
“…The neutrons propagating the chain reaction remain energetic, or fast. Fast reactors are more flexible in the type of fuel they can consume and can, for example, use uranium-238 as fuel, which is 140 times more abundant than uranium-235 (Cochran et al 2010). 4.…”
Section: Notesmentioning
confidence: 99%
“…5 Expert reviews, though, have also found technical problems with fast reactors, in particular sodium leaks, which, while not deadly, have made past reactors prone to shutdowns, which increases the cost of electricity produced (Pillai and Ramana 2014). And though liquid sodium has some safety advantages as a coolant, it also reacts violently with water and burns if exposed to air; liquid-sodium-cooled fast reactors have been shut down for long periods by sodium fires (Cochran et al 2010). The problems could get even more serious.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The FBR, however, needs fuel with a much higher concentration of fissile material; 14% is assumed in the MIT study (2011). As an alternative to plutonium, we assume that uranium enriched to 20% (highly enriched uranium [HEU]) could be used to operate these reactors based on Cochran et al (2010). This, however, has been tested on a very limited scale.…”
Section: Performance and Cost Of Technologiesmentioning
confidence: 99%
“…The breeder reactor concept has generally only been tested on a limited scale, but breeding ratios above unity, the production of a greater amount of fissile material than consumed, have been achieved in many countries and reactor types (Cochran, et al 2010). In our model, due to the lack of extensive data related to FBR fuel economy, we assume a breeding ratio of 1 and base our costs on sodium cooled reactors.…”
Section: Performance and Cost Of Technologiesmentioning
confidence: 99%